Rapid Communication: The Accreditation Council of Business Schools and Programs 2023 Conference (ACBSP’23), “Celebrating Collaborative Alliances: Stronger Together” - Miller, Alfred Howard (Journal of Ecohumanism, 2025)
The business accreditation conference, ACBSP 23, held in Chicago, June 29 through July 2, 2023, had about 750 participants, with nearly 100 sessions and 100 speakers. This conference note is an oﬃcer’s reﬂection on the event from the perspective of one of the officers, the Treasurer of ACBSP Region 8, the International Council of Business Schools, and Programs. ACBSP Region 8, the International Council of Business Schools and Programs is celebrated for it’s history via the ACBSP Region 8 Journal leading up through the first three ACBSP International Conferences, and onto Dubai 2016, where the editorship passed to me, dr. Alfred Howard Miller.